Dependence of attenuation of ionizing radiaion on compression and dimension of geologic material (an application to X-ray shielding) (2011)
"Search for alternative materials required for shielding ionizing radiation has being on the increase for some period of time. Lead which is widely used is expensive, therefore researches has to be carried out on other materials. Clay has been suggested but it is not as effective as lead in shielding ionizing radiation. This work therefore studies the compression of clay samples at different pressures and thicknesses, so as to improve its shielding ability in the attenuation of ionizing radiations. The research work was on pure clay material and studied their effectiveness as radiation shielding material. The samples were made in bricks and their linear attenuation coefficients were measured at two different X-ray energies of 60keV, 10 mA and 120 keV, 15 mA. The samples were compressed at a pressure of 875Nm-2, 1750 Nm-2, 2625 Nm-2, 3500 Nm-2, and 4375 Nm-2, for thicknesses of 1.0cm, 1.5cm, 2.0cm, 2.5cm,and 3.0cm. The result obtained shows that as the thicknesses increases, the linear attenuation increases which is in conformity with Lambert beer’s equation. The attenuation coefficient obtained shows increase in value when compared to ordinary clay samples that were irradiated without compression. "